Roles of CD133 in microvesicle formation and oncoprotein trafficking in colon cancer. Issue 3 (6th December 2018) - Kang, Minsoo; Kim, Suhyun; Ko, Jesang
ABSTRACT: Extracellular vesicles contain various cellular components that are involved in tumor growth, metastasis, and immune escape. Extracellular vesicles are classified into 2 groups, namely, exosomes and microvesicles (MV). Although the formation and roles of exosomes have been studied, the exact functions of MVs and mechanisms underlying MV release are not fully understood. We found that epidermal growth factor accelerates the release of MVs from the plasma membrane by inducing NF‐κB activation and CD133 expression. The amount and sizes of budding MVs were found to be dependent on the expression level of CD133, which regulates the activities of the small guanosine 5′‐triphosphatases RhoA and Rac1. CD133‐containing MVs released from KRAS mutant colon cancer cells delivered KRAS mutant to adjacent nontumorigenic cells and activated KRAS downstream signaling. CD133‐containing MVs were found to promote the migration and invasion of adjacent cells. CD133‐containing MVs induced the development of chemoresistance by abolishing the inhibitory effects of anti‐epidermal growth factor receptor (EGFR) drugs on cell proliferation and motility in colon cancer. These results suggest that CD133 acts as a novel modulator in MV release and in oncoprotein trafficking. CD133 can serve as a therapeutic target for treatment of anti‐EGFR drug‐resistant colon cancer.—Kang, M., Kim, S., Ko, J. Roles of CD133 in microvesicle formation and oncoprotein trafficking in colon cancer. FASEB J. 33, 4248–4260 (2019). www.fasebj.org